Obraz własnego ciała współczesnej młodzieży a kultura popularna. Badania własne - Gajtkowska, Magdalena (Kultura-Społeczeństwo-Edukacja, 2013)
The author presents the outcome of her own research on the in uence of the pop culture on self-body image. In the research, di erent aspects of self-body image are taken into account: being t, healthy and being goodlooking or pretty. The analysis of the scienti c research persuades the reader that mass media are important but not the most important source of information which they use to judge? their bodies. Moreover, it is claimed that the meaning of cocalled pop culture for teenagers’ self-judgment is di erentiated, it is most important for the appearance.